Some critical issues of content sharing network - Qiang LU; Bo LIU; Hua-ping HU (Tongxin xuebao)
As a sharing platform for files,information and resources,CSN (content sharing network) possessed a very wide distribution in Internet.It did provide a great convenience for people to share various contents through Internet with the rapid development and wide application of network techniques,especially the emergence and prevalence of P2P (peer-to-peer).However,numerous malicious files,cheating information and spywares swarmed into Internet,which pose a serious threat to the security of CSN.A survey was made of some critical issues of CSN combining with the current development and research status from the perspective of network security.The critical issues include the definition and important properties,different taxonomies of types,key techniques,developing and researching trends of CSN.